Ex Vivo Differential Responsiveness to Clostridium perfringens and Lactococcus lactis by Avian Small Intestine Macrophages and T Cells - Boodhoo, Nitish; Shojadoost, Bahram; Alizadeh, Mohammadali; Kulkarni, Raveendra R.; Sharif, Shayan (Frontiers in Immunology, 2022)
Tissue resident immune system cells in the chicken intestine play a significant role in protection against pathogens. However, very little is known about these cells. The current study was conducted to further characterize chicken intestinal immune system cells. Further, this study aimed to assess the immune modulatory action of a highly-virulent Clostridium perfringens, a commonly found chicken intestinal microbe, in comparison to a non-commensal, Lactococcus lactis, on intestine-derived immune system cells. Further, we aimed to The results demonstrated a varying distribution of innate and adaptive immune cells along the avian gut-associated lymphoid tissue (GALT) in the duodenum, jejunum, ileum and cecal tonsils. In addition, steady-state and tissue-specific presence of CD25+ cells among αβ and γδ T cell subsets was assessed along the intestine. Ex vivo stimulation with C. perfringens or L. lactis resulted in a significant increase in the frequency of CD25+ T cells (γδ and αβ T cells). In addition, significantly more cell death was observed in ex vivo stimulation with C. perfringens¬, which was indirectly correlated with a decrease in macrophage activation based on nitric oxide (NO) production with no effect on lymphoid cell responsiveness as per intracellular interferon (IFN)-gamma (γ) staining. Ex vivo stimulation with L. lactis activated γδ T cells and αβ T cells, based on intracellular IFN-γ staining, while it had limited effect on macrophages. However, the ability of γδ and αβ T cells to produce IFN-γ and the ability of macrophages production of NO was rescued in the presence of L. lactis. These results demonstrate the potential application of L. lactis, as a probiotic, against virulent C. perfringens infection in chicken.